WEWENANG KEPALA DESA DALAM MENGKOORDINASIKAN PEMBENGUNAN DESA SECARA PASRTISIPATIF - Suprianto, Ardi; Syafhendry, Syafhendry (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
Lead countryside represent leader running countryside governance business, which having duty which have been arranged in regulation of republic government of number Indonesia 72 year 2005 about countryside of at section 14 article 1 that is lead countryside have duty carry out governance business, development, and social. Intention of this research is to know Authority Execution Lead Countryside of In Coordinated development in Iake Serai Regency Bengkalis Periphery Subdistrict Countryside. This Research is research qualitative is research having the character of descriptive and tend to menggunankan analyse. Population in this research is Countryside Head, Countryside Secretary, Kaur Governance, Kaur Development, Kaur Socialize, BPD, LPMD, Elite Figure and Socialize. To Lead Countryside by Aparat is Countryside use census technique, while for the society which is a lot of using formula slovin. Pursuant to research result which the writer [do/conduct] to hit Authority Execution Lead Countryside of In Coordinated Countryside Development Partisipatively in Iake Serai Regency Bengkalis Periphery Subdistrict Countryside is Is enough Executed. Expected by a countryside head improve coordination in order to the ambulatory development partisipatively and matching with wanted by society.